Answers

2014-11-17T12:01:16+08:00
Do you mean a⁻¹ * b⁻¹ = 1/ab?

If does so. YES

Remember:

a⁻¹ = 1/a¹

When the bases are different and the exponents of a and b are the same, we can multiply a and b first:

a⁻¹ * b⁻¹ = (a * b)⁻¹

Example:

3⁻² * 4⁻² = (3 * 4)⁻² = 12⁻² = 1/12² = 1/(12 * 12) = 1/144 = 0.0069444

If the bases and exponents are the same.

We can add exponents first and multiply the bases

Example:

2⁻² * 2⁻² = 4⁻² = 1/4² = 1/16 = 0.0625

If the bases are the same and exponents are not. We simply copy the bases and add the exponents

Example:

2⁻² * 2⁻³ = 2⁻² ⁺ ⁻³ = 2⁻⁵ = 1/2⁵ = 1/32 = 0.03125

And when both base and exponents are different. We should calculate the value of each bases with their exponents and then multiply

Example:

2⁻² * 3⁻³ = 1/2² * 1/3³ = 1/4 * 1/27 = 1/108 = 0.0925925925925...

I hope it helps

0